Діагностика поведінки та переживань в умовах професійної діяльності військовослужбовців - Коваленко, Є. С.; Kovalenko, Ye. S. (Вчені записки ТНУ імені В. І. Вернадського. Сер.: Психологія. – 2023. – Т. 34 (73), № 1. - С. 178-183, 2023)
Досліджено особливості типів поведінкових реакцій у військовослужбовців з ненормативною та умовно нормативною поведінкою. Встановлено, що в респондентів з ненормативною поведінкою було виявлено прагнення дистанціюватися стосовно проблеми, яка виникає в ході діяльності та спонукає їх уникнути її розв’язання. Для першої групи характерна тенденція до відмови від своїх намірів, якщо вони відчувають невпевненість у собі та сумніваються в успішності даного заходу. Це позначається на їх показниках задоволеності життям та обумовлене відсутністю підтримки з боку навколишніх. Другу групу військовослужбовців з нормативною поведінкою можемо охарактеризувати як мотивованих, готових до енергетичних затрат осіб, котрі усвідомлюють важливість своєї діяльності. Цим досліджуваним властива активна стратегія при розв’язуванні проблемних ситуацій, що говорить про їх високу самовіддачу роботі, однак, це може призвести до перевтомлення. У першій групі 17.3% мають низький рівень у показниках професійних домагань, однак для 60.9% респондентів з ненормативною поведінкою властиві високий рівень готовності до енергетичних затрат. У понад 80% респондентів другої групи виявлені високий рівень у показниках професійних домагань та у прагненні до професійної досконалості.

The article demonstrates a concise theoretical overview of the characteristics of behavior in situations of professional requirements. The behavior of military personnel can be viewed through the lens of professional self-sufficiency, mental stability, emotional restraint, coping strategies, and legal intolerance. The purpose of the study is to investigate the specific types of behavioral reactions in servicemen with non-normative and conditionally normative behavior. The research sample consisted of 200 military personnel. The survey was conducted in January-February 2022. The groups were formed according to the indicator of their committing a disciplinary offense. The first group is servicemen with irregular behavior (having disciplinary violations), numbering 98 people. The second group is a control group, it included 102 servicemen with conditionally normative behavior. The questionnaire "Work-Related Behavior and Experience Pattern" by U. Schaarschmidt and A. Fischer was used in the work. In the course of the empirical study, it was established that the respondents with non-normative behavior showed a desire to distance themselves from the problem that arises during the activity and prompts them to avoid its solution. The first group is characterized by a tendency to abandon their intentions if they feel insecure and doubt the success of the given event. This affects their life satisfaction indicators and is due to the lack of support from those around them. The second group of servicemen with normative behavior can be characterized as motivated, ready to spend energy, people who are aware of the importance of their activities. These subjects have an active strategy in solving problem situations, which indicates their high dedication to work, however, this can lead to overwork. In the first group, 17.3% have a low level of indicators of professional harassment, but 60.9% of respondents with non-normative behavior have a high level of readiness for energy costs. More than 80% of the respondents of the second group showed a high level of indicators of professional harassment and striving for professional excellence.

Исследованы особенности типов поведенческих реакций у военнослужащих с ненормативным и условно нормативным поведением. Установлено, что у респондентов с ненормативным поведением было выявлено стремление дистанцироваться по поводу проблемы, которая возникает в ходе деятельности и побуждает их избежать ее решения. Для первой группы характерна тенденция к отказу от своих намерений, если они испытывают неуверенность в себе и сомневаются в успешности данного мероприятия. Это сказывается на их показателях удовлетворенности жизнью и обусловлено отсутствием поддержки со стороны окружающих. Вторую группу военнослужащих с нормативным поведением можем охарактеризовать как мотивированных, готовых к энергетическим затратам лиц, осознающих важность своей деятельности. Этим исследуемым свойственна активная стратегия при разрешении проблемных ситуаций, что говорит об их высокой самоотдаче работе, однако это может привести к переутомлению. В первой группе 17,3% имеют низкий уровень в показателях профессиональных притязаний, однако для 60,9% респондентов с ненормативным поведением свойственны высокий уровень готовности к энергетическим затратам. У более чем 80% респондентов второй группы выявлен высокий уровень в показателях профессиональных притязаний и в стремлении к профессиональному совершенству.
Diagnostics of behavior and experiences in the conditions of the professional activities of military servants
Коваленко, Є. С. Діагностика поведінки та переживань в умовах професійної діяльності військовослужбовців / Коваленко Є. С. // Вчені записки ТНУ імені В. І. Вернадського. Сер.: Психологія. – 2023. – Т. 34 (73), № 1. - С. 178-183. - DOI: https://doi.org/10.32782/2709-3093/2023.1/29.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; військовослужбовці; military personnel; военнослужащие; ненормативна поведінка; abnormal behavior; ненормативное поведение; правова толерантність; legal tolerance; правовая толерантность; стратегії подолання; coping strategies; стратегии преодоления; умовно нормативна поведінка; conditionally normative behavior; условно нормативное поведение; професійна діяльність; professional activity; профессиональная деятельность